Option values under stochastic volatility: Theory and empirical estimates - Wiggins, James B. (Journal of Financial Economics, 1987)
This paper numerically solves the call option valuation problem given a fairly general continuous stochastic process for return volatility. Statistical estimators for volatility process parameters are derived, and parameter estimates are calculated for several individual stocks and indices. The resulting estimated option values do not differ dramatically from Black-Scholes values in most cases, although there is some evidence that for longer-maturity index options, Black-Scholes overvalues out-of-the-money calls in relation to in-the-money calls.